Educação para a saúde no Brasil: o caso do Distrito Federal - Odete Ferreira de Amorim (1989)
This study refers to the Health Education as part of the curriculum of schools 1 ° and 2 ° degrees in Brazil. 1) History of Health Education in Brazil, Shape - chronologically from the colonial to the present day.2) Compliance Assessment and processing of statutory requirements for health education in 1 ° and 2 °. For the study, 82 public schools and private Federal District were selected by probabilistic process. Data were collected through interviews and direct observations in each school. It was found that throughout the historical process, initiatives and collective actions in this area that, attuned to the realities of the people, take place or took place in a shy way, unconnected, isolated and reduced. Often these initiatives or actions has been made in control and manipulation of small but powerful groups. It was found in schools 1 and 2 degrees, non-compliance with laws and serious flaws in the implementation of education for Health In data analysis, some results are re1evantes:A) There was no specific training for the health or for the coordination of health education in all schools surveyed. B) Most of the professionals interviewed did not express the basic principles of the WHO concept of health. C) The "Hygienic Conditions" public schools were classified as poor in 50.0% 0 25.0% reasonable. D) In the opinion of respondents, and the infrequency of low-income students are a reflection of poor health in the community. E) Most public schools are aimed mainly infectious and parasitic diseases, diseases of the digestive tract, and symptoms, signs and ill-defined conditions. F) Services to assist the students are evaluated as unsatisfactory and insufficient in most public schools.G) It was found that there is joint planning in almost all the schools visited for Health Education and the criteria for selection of content is not declared. H) The practical activities, these are not developed in more than half of schools especially in the second degree. I) Only 28.1% of schools surveyed engaged in some kind of rapport with health services, agencies, institutions and communities, highlighting schools there first degree (1st the fourth series). J) The most frequently cited form of rapport is the request for assistance to health services